Genetic association study of ERBB4 SNP rs1351592 with polycystic ovary syndrome in Pakistani population - Tayyaba Afzal; Ghazala Kaukab Raja; Maimoona Afzal; Shakeel Ahmad; Nighat Sultana; Umm e Kalsoom (Journal of the Pakistan Medical Association, 2020)
Polycystic ovary syndrome (PCOS) is an oligogenic condition, characterised by hyperandrogenism, ovulatory dysfunction and polycystic ovarian morphology. Previously, European and Han Chinese populations identified different susceptibility loci, of which ERBB4 (rs1351592) was strongly associated with PCOS. Our study aimed to investigate the association of ERBB4 Single Nucleotide Polymorphism (SNP), rs1351592 with PCOS in Pakistani women of Hazara region. Fifty PCOS patients and 14 healthy women were recruited and SNP was replicated using ARMS-PCR and sequencing. The study showed that Luteinising Hormone (LH), Follicle Stimulating Hormone (FSH), and Testosterone (T) were significantly elevated in patients compared to controls (P <0.05). Overall, the frequency of G allele was higher than C allele and the SNP lacked significant association with PCOS. This is the first study demonstrating the association of ERBB4 SNP, rs1351592 with PCOS in Pakistani population. Further research, Continuous....